P59 Two-year outcomes of using a stepwise thrombolysis protocol for the management of acute non-malignant portomesenteric thrombosis. (20th September 2022) - Hashim, Ahmed; Pandya, Aashish; Alviri, Naz Kanani; Old, Hannah; King, Jonathan; China, Louise; Yu, Dominic; Patch, David
Abstract : Introduction: Acute extensive non-malignant non-cirrhotic portomesenteric thrombosis can lead to bowel infarction and frequently does not resolve with anticoagulation. In 2019 we published our first case series of a stepwise thrombolysis protocol involving the use of low dose tissue plasminogen activator (L-tPa) followed, if indicated, by Catheter-Directed Thrombolysis (CDT) and Transjugular Intrahepatic Portosystemic Shunt (TIPSS). We present an updated series, aiming to explore the recanalization rates, symptom resolution and any adverse events for patients who received this protocol. Method: We retrospectively reviewed the clinical records of patients who received the stepwise regimen at Royal Free Hospital between December 2019 &amp March 2022. Results: A total of 35 patients were included with a mean age of 47 (SD=14) years; 63% were males. Thrombophilia was identified in 13 (37%) cases and 14 (40%) had other local or systemic causes for thrombosis (1 had COVID-19; 3 received ChAdOx1 vaccination). Three patients had underlying chronic liver disease. All patients had ongoing abdominal pain despite anticoagulation. Occlusive portal vein thrombosis (PVT) was found in 30 (86%) patients with 18 (51%) having thrombosis of all three vessels (PVT + splenic vein + superior mesenteric vein). While all patients received L-tPa within a median of 15 (IQR =18) days of symptoms, CDT was applied in 17 (49%) patients and TIPSS was inserted in 15 (43%). CDT was delivered through EKOS™ endovascular system in 11/17 (65%). A degree of recanalization was observed in 24 (69%). TIPSS was patent at discharge in 14/15 (93%). The majority 28 (80%) were maintained on warfarin and 11 had concomitant anti-platelet therapy. Fifteen patients had imaging follow-up available [median duration of 9 (IQR = 11) months]. Recanalization was maintained in 9/15 (60%) and TIPSS remained patent in 6/9 (67%). At a median follow up of 6.5 (IQR = 9) months, complete symptom resolution was achieved in 30/34 (88%). Nine patients underwent bowel resection within a median duration of 11 (IQR= 10.5) days from presentation; mean length of bowel resected was 67 cm (SD = 50). One patient was discharged on parenteral nutrition and had a stoma. One patient died during the initial admission (related to bowel ischemia) and 1 had intracranial haemorrhage. Minor bleeding was recorded in 8 patients. Conclusion: Our protocol resulted in good recanalization and patency rates with the majority achieving symptom resolution. While some patients required surgical intervention, bowel continuity was maintained and only one patient had a stoma.